Dermatosparaxia em um ovino: achados clínicos, anatomopatológicos e moleculares - Oliveira, Mariana Correia; Raimunda, Bruna Patrícia Siqueiro; Silveira, Carla Ribeiro; de Souza, Bruno Gonçalves; Ubiali, Daniel Guimarães; de Andrades, Danilo Giorgi Abranches; de Oliveira-Filho, José Paes; Brito, Marilene de Farias (Acta Scientiae Veterinariae, 2017)
Background: Dermatosparaxis is an autosomal recessive genetic disease that affects the connective tissue of animals. Collagen proteins form fibrillar structures that provide strength and structure to the extracellular matrix of tissues and organs in the body. Therefore, changes in collagen synthesis result in hyperextensibility and skin fragility. Similar to dermatosparaxis in animals, some cases of Ehlers-Danlos syndrome type VIIC have been reported in humans. The objective of this study was to describe the clinical, anatomopathological, and molecular findings of a case of dermatosparaxis in a sheep bred by crossing the Santa Inês and White Dorper breeds. Case: A case of dermatosparaxis was reported in a 20-day-old female sheep, a cross between the Santa Inês and White Dorper breeds. The sheep exhibited hyperextensibility of the skin with minimal tension and increased joint volume shortly after birth. Because of clinical worsening and the poor prognosis of the disease, the owners opted for euthanasia. The necropsy revealed large ulcerated areas in several parts of the body, including the cervical, sternal, scapular, and thoracic regions, and the inner and outer thighs. The skin was extremely easy to be removed during the necropsy and the use of a scalpel was not necessary. Extensive areas of hemorrhage were observed in the subcutaneous tissue and small intestine. The histopathological findings of the skin lesions evidenced the presence of dermatosparaxis, particularly regarding the disorganization of collagen fibers. The tests involving Masson’s trichrome staining, picrosirius red staining, and Gomori’s trichrome staining under polarized light evidence of collagen fiber dysplasia. Discussion: The diagnosis of dermatosparaxis in this study was based on clinical, anatomopathological, and molecular analysis. Molecular diagnosis was confirmed by identification of SNP c.421G>T on the ADAMTS2 gene in both the mother and the sheep under study. In humans, in addition to hyperextensibility and skin fragility, other rare clinical signs include ligamentous laxity, bone abnormalities, vascular abnormalities, uterine rupture, ocular abnormalities, and extensive areas of hemorrhage in the intestine. In this case, the humeral-radial-ulnar joints of both thoracic limbs were substantially enlarged and, when sectioned, a moderate amount of dark yellow fluid was released. Dermatosparaxis is well documented in the White Dorper sheep breed. In the present study, the genetic test revealed that the mother (Santa Inês breed) was heterozygous and phenotypically normal. All the rams in the animal herd (White Dorper breed) were phenotypically normal. Extensive hemorrhage in organs of the abdominal cavity and the high likelihood of skin rupture have been reported in other species that are affected by the disease. The histopathological findings of cutaneous lesions in this sheep agree with the descriptions in the literature on the disorganization of collagen fibers. The tests involving Masson’s trichrome staining, Gomori’s trichrome, and picrosirius red staining under polarized light were crucial for providing evidence of collagen fiber dysplasia. Even when phenotypically normal, the heterozygous sheep in the herd can produce recessive homozygous animals, which may be clinically affected, mainly, if there is a history of uncontrolled crossing in the herd.